Machine learning‐based H.264/AVC to HEVC transcoding via motion information reuse and coding mode similarity analysis. Issue 1 (1st January 2019) - Lin, Hongwei; He, Xiaohai; Qing, Linbo; Su, Shan; Xiong, Shuhua
Abstract : High‐efficiency video coding (HEVC), which is the latest video coding standard, is expected to have a dominant position in the market in the near future. However, most video resources are now encoded using the H.264/AVC standard. Consequently, there is a growing need for fast H.264/AVC to HEVC transcoders to facilitate the migration to the updated standard. This paper proposes a fast H.264/AVC to HEVC transcoding scheme, which constructs a three‐level classifier using an optimised tree‐augmented Naive Bayesian approach to predict the HEVC coding unit depth. A feature selection method is then proposed to improve prediction accuracy. A motion vector (MV) calculation method is also proposed to reduce the complexity of MV prediction in HEVC by reusing MVs from H.264/AVC. Experimental results show that, compared with other state‐of‐the‐art transcoding algorithms, the proposed algorithm considerably reduces coding complexity while causing only negligible rate‐distortion degradation.